2017
DOI: 10.3390/met7040113
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies on Local Reinforcement of Sheet Metal Components by Laser Additive Manufacturing

Abstract: This paper details two case studies that make use of laser metal deposition for local reinforcement of sheet metal components. Two benchmark scenarios are investigated, both using aluminum alloys: (i) using laser cladding to increase the stiffness of a pre-formed component, and (ii) applying a local cladding on sheet metal for increasing the thickness prior to a hole-flanging operation. The results show that both routes are viable. Applying claddings onto sheet metal before a metal forming operation must ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…The previously mentioned increased raw material efficiency of AM also effects the environmental sustainability positively (Attaran 2017;Bambach et al 2017;Ben-Ner and Siemsen 2017;Chiu and Lin 2016;Faludi et al 2015;Ford and Despeisse 2016). Not only is less raw material required but it can also be transported in powder form which allows a more efficient space utilisation and yields a reduction of carbon emissions .…”
Section: Environmental Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The previously mentioned increased raw material efficiency of AM also effects the environmental sustainability positively (Attaran 2017;Bambach et al 2017;Ben-Ner and Siemsen 2017;Chiu and Lin 2016;Faludi et al 2015;Ford and Despeisse 2016). Not only is less raw material required but it can also be transported in powder form which allows a more efficient space utilisation and yields a reduction of carbon emissions .…”
Section: Environmental Sustainabilitymentioning
confidence: 99%
“…Due to the design freedom of AM, the consolidation of separate parts into one more complex part becomes possible (Weller, Kleer, and Piller 2015;Waller and Fawcett 2014;Wagner and Walton 2016;Strange and Zucchella 2017;Rylands et al 2016;Mothes 2015;Kellens et al 2017; Ben-Ner and Siemsen 2017; Grzesiak, Becker, and Verl 2011; Knofius, van der Heijden, and Zijm 2019a). Overall, products could even be of higher quality with novel designs that were previously not feasible (Bambach et al 2017;Kellens et al 2017).…”
Section: Product Designmentioning
confidence: 99%
See 1 more Smart Citation
“…These features, such as cooling or reinforcement ribs or other structural or functional elements are then added via AM. Bambach et al [13] showed that AM can be used to create local reinforcements on sheet metal parts. Extensive work on additively manufactured features which are added to formed parts have been performed by Merklein et al [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…While Gabriel et al [18] used an ytterbium-fiber laser with powers up to 82 W to clad cobalt-based powder onto Inconel 718 substrates with a thickness of 0.2 mm, Tebaay et al [19] investigated the use of a 2.5 kW diode-laser for cladding of AISI 316L powder on a DC01 sheet in either cold-rolled steel or a condition after incremental sheet-forming. The use of laser cladding for reinforcement of aluminum [20] or steel sheets [21,22] prior to forming operations has also recently attracted pronounced attention.…”
Section: Introductionmentioning
confidence: 99%